Surgical interventions for degenerative cervical disease: Impact on patient quality of life, mental health, pain relief, and spiritual health - Ching-Ya Huang; Cheng-Shyuan Rau; Jo-Chien Lin; Shiun-Yuan Hsu; Ching-Hua Hsieh (Heliyon)
Introduction: Degenerative cervical diseases can severely affect patients' quality of life (QOL), mental health, and physical function. While surgical intervention is a common treatment, its impact on holistic well-being, including spiritual health, has not been thoroughly explored. This study aimed to evaluate the effects of surgery on QOL, pain-related disability, mental health, and spiritual well-being in patients with degenerative cervical diseases. Methods: This prospective cohort study was conducted with a purposive sampling of thirty-five patients who were diagnosed with degenerative cervical diseases and consented to surgery. The outcomes were assessed using the 36-item Short Form Health Survey Quality of Life Scale (SF-36), Patient Health Questionnaire-9 (PHQ9), Pain Disability Questionnaire (PDQ), and Holistic Well-being Scale (HWS) scales before surgery and six months postoperatively. The study focused on measuring the changes in patients’ physical and mental health, pain disability, and spiritual well-being, using paired sample t-tests. Results: Post-surgery, patients exhibited significant improvements in all domains of the SF-36 scores. Depression scores decreased as indicated by a reduction in PHQ-9 scores (from 18.54 to 15.00, P = 0.001). PDQ scores showed significant reductions in pain-related disability (from 79.00 to 50.26, P < 0.001). However, while there were improvements in emotional vulnerability (HWS score from 4.48 to 4.10, P = 0.020) and in the overall affliction score (from 4.45 to 4.11, P = 0.015), there were no significant changes in body irritability or spiritual disorientation within the affliction domain, nor in any of the items related to equanimity in holistic well-being. Conclusion: Surgical intervention for degenerative cervical diseases significantly improves patients’ QOL, mental health, and pain-related disability, but the impact on spiritual well-being is limited. This suggests that postoperative care should adopt a more holistic approach, integrating mental and spiritual support. Future research should include a more diverse sample, longer follow-up periods, and a combination of subjective and objective measures for a comprehensive assessment of outcomes.